2019
DOI: 10.1002/chem.201902801
|View full text |Cite
|
Sign up to set email alerts
|

Basal Histamine H4 Receptor Activation: Agonist Mimicry by the Diphenylalanine Motif

Abstract: Histamine H4 receptor (H4R) orthologues are G‐protein‐coupled receptors (GPCRs) that exhibit species‐dependent basal activity. In contrast to the basally inactive mouse H4R (mH4R), human H4R (hH4R) shows a high degree of basal activity. We have performed long‐timescale molecular dynamics simulations and rigidity analyses on wild‐type hH4R, the experimentally characterized hH4R variants S179M, F169V, F169V+S179M, F168A, and on mH4R to investigate the molecular nature of the differential basal activity. H4R vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

6
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…We combined extensive MD simulations in combination with a rigidity theory-based free energy perturbation approach to scrutinize the role of dynamic, i.e., entropically dominated, allostery for cooperativity within and between the CL-CNBDs of the subunits, study signal transmission evoked by bound cAMP, and identify interactions involved in the signaling. The rigidity theory-based free energy perturbation approach (20) proved successful in related studies of membrane proteins (40)(41)(42). Our results allowed us to map out distinct routes within the tetrameric CL-CNBD that modulate different cAMP binding responses in HCN2 channels through disjunct salt bridge interactions.…”
Section: Discussionmentioning
confidence: 88%
“…We combined extensive MD simulations in combination with a rigidity theory-based free energy perturbation approach to scrutinize the role of dynamic, i.e., entropically dominated, allostery for cooperativity within and between the CL-CNBDs of the subunits, study signal transmission evoked by bound cAMP, and identify interactions involved in the signaling. The rigidity theory-based free energy perturbation approach (20) proved successful in related studies of membrane proteins (40)(41)(42). Our results allowed us to map out distinct routes within the tetrameric CL-CNBD that modulate different cAMP binding responses in HCN2 channels through disjunct salt bridge interactions.…”
Section: Discussionmentioning
confidence: 88%
“…This also includes structural water molecules, metal ions, and cofactors, which can be considered in the analysis. Finally, CNA has been used to understand signal propagation [54] and allosteric effects [55] , [56] within biomolecules, primarily within membrane proteins, expanding the application scope of CNA.…”
Section: Resultsmentioning
confidence: 99%
“…4A). A recent study indeed reported roles of ECL2 in modulating class A GPCR basal activity 29 . Fig.…”
Section: Fig 3 In Vitro Basal Activities (A)mentioning
confidence: 94%